Three essays on development and labor economics - Ma, Cheng (My University, 2022)
Chapter 1 examines the causal relationship between family size and upstream intergenerational transfers. Successful family planning policies in China not only led to a dramatic decrease in fertility rate but also raised concerns about whether a smaller family-based elderly care network can provide adequate financial support. The relationship between family size and transfers needs more exploration. However, the endogeneity of family size hindered past studies from establishing a causal effect of family size on transfers. This chapter exploits the variations in the strictness of the One Child Policy implementation to address this endogeneity. Using the data from the China Health and Retirement Longitudinal Study (CHARLS), our estimation suggests that family size does not have an effect on either the probability of receiving transfers or the amount of transfers from children, which can be explained by both quantity-quality trade-off and parental financial need. In addition, our findings suggest that higher parental financial need explains the heterogeneity in effect of family size on transfers between urban households and rural households. Moreover, the inconsistency between our results and the literature is indicative of the heterogeneous nature of the effect of family size on transfers. Chapter 2 studies the return to spousal education. Although a body of literature has extensively investigated the relationship between spousal education and one's earnings, a causal relationship is rarely established. This occurs because of the failure to address the endogeneity of spousal educational attainment. In this chapter, we use a method that utilizes the nonlinearity of control terms induced by heteroskedasticity to estimate the causal effect of spousal education on one's own earnings. Using the data from the Chinese Household Income Project (CHIP), our estimation suggests that spousal schooling has a sizable positive effect on one's earnings. We find that spousal education increases one's earnings by raising hourly wages rather than lengthening work hours. Our findings also suggest that there exists substantial heterogeneity in return to spousal education by gender, by spousal education level, by year, by dominant earner status, and by whether spouses share the same occupation. Chapter 3 is coauthored with Gabe Lebovich. In this chapter, we test the effect of additional children in a family on health and educational outcomes. Estimating this effect is complicated by the endogeneity of family size. We use the variation in the severity of the effect of the one-child-policy in China to extract exogenous variation from the China Health and Nutrition Survey in the same country. After finding a negative effect of family size on health and educational outcomes of children we use a newly developed machine learning approach. Generalized random forests allows us to look at the heterogeneity in treatment effects in the quantity-quality trade-off. We find robust negative treatment effects of additional children on health outcomes but only mild effects on educational attainment. The machine learning algorithm finds mother's age and parent's education level play a large role in the negative quantity-quality trade-off. Pinpointing the factors that exacerbate the negative effect of additional children on child quality can aid future policy decisions.
Keywords: elderly support; spousal education; quantity-quality trade-off